2005
DOI: 10.3354/meps292111
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macrofaunal communities of three sites in San Francisco Bay invaded by hybrid Spartina, with comparison to uninvaded habitats

Abstract: A hybrid cordgrass, formed from a cross between Spartina alterniflora (Atlantic cordgrass) and S. foliosa (Pacific cordgrass), has recently spread within the intertidal zone of south San Francisco Bay. Sediment properties and macroinfaunal community structure were compared in patches invaded by Spartina hybrid and adjacent uninvaded patches at 3 sites in San Francisco Bay (2 tidal flats and 1 Salicornia marsh). We hypothesized that (1) sediments vegetated by Spartina hybrid would have reduced sediment grain si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
143
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 48 publications
9
143
0
Order By: Relevance
“…Expanding S. anglica marshes appeared hospitable for native macroinvertebrates in Little Swanport estuary, Australia (Hedge and Kriwoken 2000) and Paranagua Bay, Brazil (Netto and Lana 1999). On the other hand, negative eVects similar to those observed in the present study have been reported at various locations, such as San Francisco Bay (Neira et al 2005), southwest Netherlands (Gribsholt and Kristensen 2003) and south coast of Britain (Frid and James 1989). In many of these latter cases, the response has been attributed to diVerences in the below-ground plant biomass (Brusati and Grosholz 2006).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Expanding S. anglica marshes appeared hospitable for native macroinvertebrates in Little Swanport estuary, Australia (Hedge and Kriwoken 2000) and Paranagua Bay, Brazil (Netto and Lana 1999). On the other hand, negative eVects similar to those observed in the present study have been reported at various locations, such as San Francisco Bay (Neira et al 2005), southwest Netherlands (Gribsholt and Kristensen 2003) and south coast of Britain (Frid and James 1989). In many of these latter cases, the response has been attributed to diVerences in the below-ground plant biomass (Brusati and Grosholz 2006).…”
supporting
confidence: 86%
“…Hacker et al 2001;Cottet et al 2007). Much work has been undertaken on the changes of invertebrate macrobenthic assemblages associated with Spartina saltmarshes in North America (Levin and Talley 2000;Neira et al 2005;Brusati and Grosholz 2006), while there is only limited information from northern Europe (Vinther et al 2001;Gribsholt and Kristensen 2003). The Wadden Sea is treasured by its special native biodiversity and is a stepping stone for a variety of migratory waterbirds (Vinther et al 2001;Loebl et al 2006).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The effect of structural complexity of macrophyte vegetations like seagrasses and salt marsh species, have been well described with respect to protection from predation, reduction of current velocity, retention of particle and the accretion of sediment. Several studies show that these physical changes tend to increase macrofaunal species richness and/or abundances (seagrasses : Orth 1992;Heck et al 1995;Bartholomew, 2002;salt marsh plant: Rader 1984;Netto et al 1997, Netto andLana 1999;Whaley and Minello 2002;Brusati and Grosholz 2006), but with exceptions, especially for the salt marsh species (e.g., Moseman et al 2004;Neira et al 2005;Levin and Talley 2000). The contrasting influence of Spartina species on macrobenthos composition may be due to conditional outcomes of ecosystem engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a shift in benthic assemblages, birds may also not able to physically reach benthos living in the marsh vegetation. Researchers studying invasive Spartina have reported altered faunal composition and abundance (e.g., Hedge and Kriwoken 2000;Neira et al 2005) and trophic function .…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear whether such species, termed invasive on the basis of their impact on ecosystems lacking similar functional groups, have a strong, or any, impact on communities where functionally similar native species are also present. Comparison of benthic macrofaunal communities associated with an invasive and a native habitat-forming cord grass, for example, showed no difference in assemblages, demonstrating that both species are functionally similar in terms of biodiversity facilitation (Neira et al, 2005).…”
Section: Introductionmentioning
confidence: 98%